2005
DOI: 10.1111/j.1439-0442.2005.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Urinary and Mammary Excretion of Ceftriaxone in Lactating Goats

Abstract: The pharmacokinetic properties of ceftriaxone were investigated in 10 goats following a single intravenous (i.v.) and intramuscular (i.m.) administration of 20 mg kg(-1) body weight. After i.v. injection, ceftriaxone serum concentration-time curves were characteristic of a two-compartment open model. The distribution and elimination half-lives (t(1/2alpha), t(1/2beta)) were 0.12 and 1.44 h respectively. Following i.m. injection, peak serum concentration (C(max)) of 23.6 microg ml(-1) was attained at 0.70 h. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 31 publications
13
22
0
Order By: Relevance
“…There is little literature related to effect of herbal drugs on pharmacokinetics of antimicrobial agents following intramammary administration particularly for ceftriaxone. Though the pharmacokinetic study of ceftriaxone was undertaken in many species following parenteral administration, e.g., cow calves (6) , buffalo calves (7) , lactating ewes (8) and lactating goats (5,9) , pharmacokinetic data following intramammary administration of ceftriaxone is unavailable. Hence, our present study was conducted to determine the plasma and milk level of ceftriaxone and/or ceftizoxime following single dose intramammary administration of ceftriaxone with 1 h pre-single dose oral administration of Fibrosin ® .…”
Section: Introductionmentioning
confidence: 99%
“…There is little literature related to effect of herbal drugs on pharmacokinetics of antimicrobial agents following intramammary administration particularly for ceftriaxone. Though the pharmacokinetic study of ceftriaxone was undertaken in many species following parenteral administration, e.g., cow calves (6) , buffalo calves (7) , lactating ewes (8) and lactating goats (5,9) , pharmacokinetic data following intramammary administration of ceftriaxone is unavailable. Hence, our present study was conducted to determine the plasma and milk level of ceftriaxone and/or ceftizoxime following single dose intramammary administration of ceftriaxone with 1 h pre-single dose oral administration of Fibrosin ® .…”
Section: Introductionmentioning
confidence: 99%
“…Research on the penetration of ceftriaxone antibiotics from blood into milk produced by normal and/or mastitic mammary glands is rare. There are data for ceftriaxone concentration in the milk of goats (Ismail, 2005); however, no data are available for its behaviour in sheep milk. The presence of drug residues in milk may have public health implications, and is perceived by consumers as undesirable.…”
Section: Introductionmentioning
confidence: 99%
“…Ceftizoxime, a broad spectrum antibiotic is effective against a wide variety of aerobic/anaerobic gram positive and gram negative bacteria and remains highly stable in presence of β lactamases. It was reported that a lower concentration of ceftriaxone is excreted in milk of goats following single dose intravenous and intramuscular administration at 20 mg kg −1 body weight 7 . However, ceftizoxime was detected in milk at an appreciable level for 720 hr and 24 hr post dosing, respectively following intravenous and intramuscular dosing of ceftriaxone at 50 mg kg −1 in lactating goats 5,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be expected that the polyherbal drug will enhance excretion of ceftizoxime from milk compartment shortening the persistence of eftizoxime residue in milk after achieving higher concentration for a certain period of time during the late hours following single intravenous dosing of ceftriaxone. Though the pharmacokinetic study of ceftriaxone was conducted in many ruminant species following parenteral administration, e.g., sheep 10 cow calves 11 , crossbred calves 12,13 , buffalo calves 14,15 , lactating goats 3,5,7 and crossbred mastitic cows 6 but disposition study of its active metabolite, e.g., ceftizoxime to determine pharmacokinetic parameters in milk following intravenous dosing of the parent ceftriaxone was not done. Dosing interval of antibacterial drug in mastitis or other bacterial infections also should be based on maintenance of therapeutic concentration of its active metabolite at the site of infection e.g., mammary gland/milk in mastitis particularly when the metabolite is the major active metabolite of the parent drug and when the active metabolite, not the parent drug excretes through milk at a higher rate.…”
Section: Introductionmentioning
confidence: 99%